Pengembangan Media Pembelajaran Modul Interaktif Pada Materi Jurnal Khusus Pendidikan Ekonomi Universitas Muhammadiyah Bengkulu - Selviani, Ayudho; Ranisa, Ranisa; Rustu Sawaludin, Muhammad; Anandyta Putri Pramesti, Meiza (Jurnal Riset Pendidikan Ekonomi, 2024)
This research aims to develop and test the effectiveness of interactive learning media modules on special journal material in the Economics Education Study Program at Universitas Muhammadiyah Bengkulu. The research method used is Research and Development (R&D), which includes the stages of needs analysis, design, development, validation, limited trials, and large-scale trials. The results of the study indicate that the use of interactive modules enhances students' understanding and motivation to learn. This module is expected to be widely implemented in the classroom learning process.